Selenium Supplementation Affects Physiological and Biochemical Processes to Improve Fodder Yield and Quality of Maize (Zea mays L.) under Water Deficit Conditions - Nawaz, Fahim; Naeem, Muhammad; Ashraf, Muhammad Y.; Tahir, Muhammad N.; Zulfiqar, Bilal; Salahuddin, Muhammad; Shabbir, Rana N.; Aslam, Muhammad (Frontiers in Plant Science, 2016)
Climate change is one of the most complex challenges that pose serious threats to livelihoods of poor people who rely heavily on agriculture and livestock particularly in climate-sensitive developing countries of the world. The negative effects of water scarcity, due to climate change, are not limited to productivity food crops but have far-reaching consequences on livestock feed production systems. Selenium (Se) is considered essential for animal health and has also been reported to counteract various abiotic stresses in plants however, understanding of Se regulated mechanisms for improving nutritional status of fodder crops remains elusive. We report the effects of exogenous selenium (Se) supply on physiological and biochemical processes that may influence green fodder yield and quality of maize (Zea mays L.) under drought stress conditions. The plants were grown in lysimeter tanks under natural conditions and were subjected to normal (100% field capacity) and water stress (60% field capacity) conditions. Foliar spray of Se was carried out before the start of tasseling stage (65 days after sowing) and was repeated after one week, whereas water spray was used as a control. Drought stress markedly reduced the water status, pigments and green fodder yield and resulted in low forage quality in water stressed maize plants. Nevertheless, exogenous Se application at 40 mg L-1 resulted in less negative leaf water potential (41%) and enhanced relative water contents (30%), total chlorophyll (53%), carotenoid contents (60%), accumulation of total free amino acids (40%) and activities of superoxide dismutase (53%), catalase (30%), peroxidase (27%) and ascorbate peroxidase (27%) with respect to control under water deficit conditions. Consequently, Se regulated processes improved fodder yield (15%) and increased crude protein (47%), fibre (10%), nitrogen free extract (10%) and Se content (36%) but did not affect crude ash content in water stressed maize plants. We propose that Se foliar spray (40 mg L-1) is a handy, feasible and cost-effective approach to improve maize fodder yield and quality in arid and semi-arid regions of the world facing acute shortage of water.